(untitled) (Pravaha, 2021)
This paper aims to analyse the provisions of expressly disallowed expenses for deduction while computing the taxable income under the income tax acts. The study uses a qualitative approach of doctrinal legal research to explain the state of affairs of past and present provisions. Consequently, it employs the primary and secondary sources of data and information from the enacted income tax Acts, Rules, journals, reports, bulletins, precedence, books, dictionaries, encyclopedias, indexes, etc. The study found the expenses that are expressly disallowed for deduction are explicit provisions in the ITA, 2002 followed by the ITA, 1974 however, the former two Acts (i.e., ITA 1960 and ITA 1962) lack the provisions of such non-deductible expenses. The result showed the latter two Acts (i.e., ITA 1974 and ITA 2002) were found adequate in the context of Nepal and they are comparatively equal to the Indian and the UK’s income tax acts. It is usual today but there are some places for improvement in this subject considering the society, culture, economy and political system in Nepal. The paper provides an explicit result of the disallowed expenses of the personal, domestic and capital nature those which are not related to earning or receiving the income. Thus, the study furnishes new knowledge in the literature on income tax in Nepal.